E-learning as valuable caregivers' support for people with dementia - A systematic review - Klimova, Blanka; Valis, Martin; Kuca, Kamil; Masopust, Jiri (BMC health services research, 2019)
BACKGROUND: Present demographic trends show a considerable rise in elderly populations with aging disorders, such as dementia. The current article focused on the exploitation of e-learning as an informal support for caregivers of people with dementia and considered its benefits and limitations to provide proper and relevant care for this target group of people as well as maintain the quality of life of their caregivers. METHODS: The methodology of this study is based on a literature review of accessible peer-review articles from three recognized databases: Web of Science, Scopus, and PubMed. The findings of the selected studies were compared and evaluated. RESULTS: The findings showed that e-learning educational programs/courses helped caregivers feel more confident about dementia care, reduced their perceived stress and enhanced their feelings of empathy, understanding and concern. CONCLUSIONS: The findings of this study reveal that the exploitation of e-learning as a support tool, especially for informal caregivers, in the management of dementia may be a promising method, but its implementation requires professional training of informal caregivers in the use of this technology. More evidence-based studies are needed on this topic.
Keywords: randomizované kontrolované studie jako téma; osoby pečující o pacienty; E-learning; Dementia; Humans; lidé; Limitations; Benefits; Computer-Assisted Instruction; počítačem řízená výuka; demence; Randomized Controlled Trials as Topic; Caregivers